2017
DOI: 10.12659/aot.905335
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Relapse After Liver Transplantation: Younger Women Are at Greatest Risk

Abstract: BackgroundAlcoholic cirrhosis is an indication for 40% of liver transplantations (LT) in Europe. In most centers, 6 months of abstinence is required before listing. However, alcohol recidivism is quite high after LT, and approximately 20–25% of recipients with ALD resume harmful drinking, resulting in liver insufficiency, which casts doubt on the 6-months rule as a reliable marker of abstinence maintenance after LT.Material/MethodsWe analyzed data on patients who underwent orthotopic LT in Marie Curie Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…The lack of proper counseling for alcohol use disorder must be addressed, as studies have demonstrated increased risk of relapse of harmful drinking among women with alcohol-related liver disease who received transplants. 24 This increased relapse for women is problematic, as it has been associated with a higher incidence of recurrent disease for women than for men.…”
Section: Managementmentioning
confidence: 99%
“…The lack of proper counseling for alcohol use disorder must be addressed, as studies have demonstrated increased risk of relapse of harmful drinking among women with alcohol-related liver disease who received transplants. 24 This increased relapse for women is problematic, as it has been associated with a higher incidence of recurrent disease for women than for men.…”
Section: Managementmentioning
confidence: 99%
“…Prior to admission, she was hospitalized in another local hospital with signs and symptoms suggesting alcoholic hepatitis. These symptoms were jaundice, hepatomegaly, tense ascites, peripheral edema, increased liver enzyme activity with the predominance of aspartate aminotransferase (AST) over alanine aminotransferase (ALT) (AST/ALT ratio >2), high gamma glutamyl transferase (GGT) activity, macrocytic anemia, elevated serum bilirubin, increased serum triglycerides, decreased serum albumin, an elevated white blood cell count, and coagulopathy [ 15 ]. After several days of hospitalization, new symptoms, including fever, dyspnea, and cough, appeared.…”
Section: Case Reportsmentioning
confidence: 99%
“…Based on the abdominal ultrasound showing liver steatosis, ascites, and hepatomegaly, as well as the laboratory abnormalities typical for alcoholic liver injury, she was diagnosed with alcoholic hepatitis with liver decompensation. The symptoms were jaundice, hepatomegaly, ascites, peripheral edema, increased aminotransferases with the predominance of AST (AST/ALT ratio >2), high GGT activity, macrocytic anemia, elevated serum bilirubin, increased serum triglycerides, decreased serum albumin, an elevated WBC count, and coagulopathy [ 15 ]. Viral infections such as HAV, HBV, HCV, and HIV were excluded after standard tests.…”
Section: Case Reportsmentioning
confidence: 99%
“…Recent studies have indicated that resumption of alcohol abuse following LT leads to significantly reduced survival rates. Patients who resumed heavy drinking have been reported to have 5- and 10-year survival rates of 69.5% and 20.1%, respectively, compared to 90.3% and 81.5%, respectively, in abstinent patients[ 7 , 190 , 199 ].…”
Section: Post-lt Outcomes In Ald Patientsmentioning
confidence: 99%
“…Based on a multivariate analysis, only two factors were independently associated with harmful relapse: Lack of prior participation in an alcohol rehabilitation program and single versus married status[ 196 ]. Younger women dependent on alcohol shortly before LT are at greatest risk of relapse[ 199 ].…”
Section: Post-lt Outcomes In Ald Patientsmentioning
confidence: 99%